SWOT-аналіз енергетичної безпеки України - Івасечко, Ольга; Дорош, Леся (Lviv Polytechnic Publishing House, 2016)
Розглянуто проблему реформування енергетичного сектору України, що викликана глобальними, регіональними та локальними тенденціями у енергетичній сфері та зміною політичних, економічних та безпекових пріоритетів України у контексті російсько-українського конфлікту. На основі аналізу “Нової енергетичної стратегії України до 2020 року: безпека, енергоефективність, конкуренція” (НЕС 2020) за допомогою методики SWOT-аналізу виокремлено переваги та недоліки енергетичної безпеки України, а також зовнішні та внутрішні загрози таможливості у цій сфері. The article considers the problemof reforming of the Ukrainian energy sector, which is caused by global trends in the energy sector and by changes of Ukrainian political, economic and security priorities in the context of the Russia-Ukraine conflict. Taking into consideration efforts of the international community in combating climate change, the research analyses Ukraine’s international obligations in the context of signing the Paris Agreement 2015 on greenhouse gases emissionsmitigation. It is emphasized that this fact, in its turn, constrains our state authorities in revising the state policy in the energy sector, taking into account the necessity to attract significant investments for implementation of the reform. Particular attention is paid to the Ukraine’s EU integration course in the energy sector, especially on harmonization (adaptation) of the Ukraine-European Union Association Agreement in this field. It is asserted that the association with the EU allows Ukraine to find new ways of creation of qualitative energy security. Based on the analysis of the “New Energy Strategy of Ukraine Until 2020: Security, Energy Efficiency, Competition” (NES 2020), the author defines strengths and weaknesses of Ukraine’s energy security, as well as its internal and external threats and opportunities. The article deals with opinions of leading Ukrainian experts on implementation of the new energy strategy. The basic formula of Ukraine’s energy security is determined as following: energy efficiency and energy saving + proper usage of its own resources + diversification of imported energy supply + creation of strategic reserves + integration into the EU energy space. Implementation of these main components will allow creating and maintaining of strong and sustainable state energy security. The article emphasises three possible scenarios of Ukrainian energy sector development until 2020: “Europeanization of Ukraine’s energy market”, “Preservation of the status quo in energy relations”, “Loss of independence in energy policy”.
SWOT-analysis of Ukraine’s energy security
Keywords: енергетична безпека; Нова енергетична стратегія України до 2020 р.; Угода про асоціацію України з Європейським Союзом; конфлікт на Сході України; energy security; New Energy Strategy of Ukraine Until 2020; the Ukraine-European Union Association Agreement; conflict in the East of Ukraine; 323.22/28